Autism and its social impact - Rodríguez-Saltos, Elisa Rafaela; Yenchong-Meza, Werme Esaud; Ponce-Solorzano, Maria Julieta (International research journal of management, IT and social sciences, 2024)
The objective that is intended to be achieved with this article is to raise awareness of Autism Spectrum Disorder linked to the various areas where the individual with ASD is presented as the main actor. One of the main characteristics that a person with Autism Spectrum Disorder has is the difficulty in communicating with other people, it affects the neurodevelopment of the person, its first symptoms begin in the first years of life, therefore the communication relationship and emotional that begins with the family is one of the main ones, here the confidence to relate to the outside world, such as school, is strengthened; The child begins to bond with people of the same age, which can be a viable strategy for the development of interpersonal intelligence. Then there is the social area, which aims to achieve good communication relationships with others, and finally, there is the world. work, where the subject is in the adult stage achieving self-sufficiency and empowerment to break barriers in their professional life.